A Novel Temperature‐Dependent Hydrogel Emulsion with Sol/Gel Reversible Phase Transition Behavior Based on Polystyrene‐co‐poly(N‐isopropylacrylamide)/Poly(N‐isopropylacrylamide) Core–Shell Nanoparticle. Issue 2 (18th November 2020) - Jiang, Yingnan; Yan, Ruyue; Pang, Bo; Mi, Jiqiang; Zhang, Yang; Liu, Hou; Xin, Jingwei; Zhang, Ying; Li, Na; Zhao, Yu; Lin, Quan
Abstract: As a kind of temperature‐responsive hydrogel, polystyrene‐ co ‐poly( N ‐isopropylacrylamide)/poly( N ‐isopropylacrylamide) (PS‐ co ‐PNIPAM/PNIPAM) core–shell nanoparticles prepared by two‐step copolymerization are widely studied and used because of their specific structures and properties. Unlike most reports about the steady stability of PS‐ co ‐PNIPAM/PNIPAM core–shell nanoparticle hydrogel emulsion, in this work, the PS‐ co ‐PNIPAM/PNIPAM core–shell nanoparticle hydrogel emulsion (symbolized as PS/PNIPAM hydrogel emulsion), which is prepared after the second step of synthesis and without washing out a large number of PNIPAM polymer segments, shows a reversible temperature‐dependent sol–gel transition characteristic during the temperature range of 34–80 °C. The PS/PNIPAM hydrogel emulsion is a normal solution at room temperature, and it changes from a sol to a gel statue when the temperature approaches up to low critical solution temperature (LCST). As the temperature continues to increase, the gel (core–shell nanoparticles as the crosslinkers and the linear PNIPAM chain as the 3D gel network) of the PS/PNIPAM hydrogel emulsion gradually shrinks and drains linearly. Compared with most crosslinked hydrogels, the hydrogel here can be arbitrarily changed in shape according to use needs, which is convenient for use, transportation, and storage. Here a new route is provided for the preparation of a PS/PNIPAM core–shell hydrogel nanoparticle system, as well as a new supramolecular crosslinking sol–gel system for application in biomedical materials, sensors, biological separation, drug release, macromolecular adsorption, and purification. Abstract : The polystyrene‐ co ‐poly( N ‐isopropylacrylamide)/poly( N ‐isopropylacrylamide) (PS‐ co ‐PNIPAM/PNIPAM) core–shell nanoparticle hydrogel emulsion, which is prepared without washing out plenty of PNIPAM polymer, shows a reversible temperature‐dependent sol–gel transition characteristic from 34 to 80 °C. It provides a new route for the preparation of PS/PNIPAM core–shell hydrogel nanoparticle system, as well as a new supramolecular crosslinking sol–gel system for various applications.